Schools and Classrooms in a Sociological Perspective - Inayah, Inayah; Widayanti, Linda; Maesaroh, Maesaroh; Mulyana, Asep; Udin, Tamsik (Journal of English Language and Education, 2026)
School and classroom are not merely educational spaces but act as dynamic arenas where social structures are reproduced and contested. While schools are expected to promote equality, sociological perspectives reveal their latent role in sustaining social inequalities. This study aims to explore how classrooms function as sites of social integration, reproduction of inequality, and identity formation. Using a qualitative library research method, this paper analyzes theories from Durkheim, Bourdieu, Foucault, Mead, and others to examine classroom dynamics. Findings show that education often legitimizes dominant cultural capital, perpetuates labeling practices, and imposes subtle disciplinary power. Classrooms become microcosms of society where power, norms, and ideologies are constructed and negotiated. The study concludes that critical awareness among educators and policymakers is vital to transform classrooms into inclusive and democratic spaces. Future studies should empirically investigate strategies that resist structural inequality within educational institutions.